Retinal Gene Delivery by rAAV and DNA Electroporation. Issue 1 (15th February 2013) - Venkatesh, Aditya; Ma, Shan; Langellotto, Fernanda; Gao, Guangping; Punzo, Claudio
Abstract: Ocular gene therapy is a fast‐growing area of research. The eye is an ideal organ for gene therapy since it is immune privileged and easily accessible, and direct viral delivery results primarily in local infection. Because the eye is not a vital organ, mutations in eye‐specific genes tend to be more common. To date, over 40 eye‐specific genes have been identified harboring mutations that lead to blindness. Gene therapy with recombinant adeno‐associated virus (rAAV) holds the promise to treat patients with such mutations. However, proof‐of‐concept and safety evaluation for gene therapy remains to be established for most of these diseases. This unit describes the in vivo delivery of genes to the mouse eye by rAAV‐mediated gene transfer and plasmid DNA electroporation. Advantages and limitations of these methods are discussed, and detailed protocols for gene delivery, required materials, and subsequent tissue processing methods are described. Curr. Protoc. Microbiol . 28:14D.4.1‐14D.4.32. © 2013 by John Wiley & Sons, Inc.